PENERAPAN MEDIA AURORA ANIMASI 3D MAKER UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MAHASISWA BIOLOGI IKIP BUDI UTOMO MALANG - Riyanto Riyanto; Lis Susilawati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
The low understanding of students in learning the Genetics of protein synthesis material. This study aims to determine the increase in cognitive learning outcomes through Aurora media 3D Maker Animation in the Genetics course of the 2016-A Biology Education Student of IKIP Budi Utomo Malang.he research approach used is qualitative and the type of research is Classroom Action Research (CAR). The instruments used were learning tools, field notes, test questions, and documentation. Data retrieval is done by formative tests. The subject of this research is the Biology student amounts to 45 students. The results showed that the application of Aurora media to 3D Maker Animation can improve the Cognitive learning outcomes of 2016-A Biology students, with cognitive learning outcomes with classical completeness 71% to 88%. Based on these data it can be concluded that the application of Aurora media 3D Maker Animation can improve the Cognitive Learning Outcomes of 2016 Biology students IBU.